THE IMPLEMENTATION OF EDUCATIONAL DECENTRALIZATION POLICY - Nurcholis, Hanif (Jurnal Ilmu Administrasi Negara, 2013)
The research explain theimplementation of educational decentralization policy in the Tangerang Regency, Banten Province,Indonesia. The research is intended to answer the question, “Why the output of the implementationof educational decentralization didn’t meet with society’s expectation”. This research used qualitativeapproach because to understand of empirical phenomenon. Based on qualitative method, researcherplays as main instrument. Observation, in-depth interview, focus group discussion, and documentarystudy were used for submitting the data. To answer of research problem, used theories of EdwardsIII. The research found that result of implement educational decentralization policy in TangerangRegency not accordance with the society’s expectation. There were five factors caused: (1) It hadnot developed operational legal framework on the function given, (2) It had not made operationalagent organization where design, enrollment, instruction, and function suitable with its functions,(3) It had not allocated their adequate fund to carry out educational service; (4) The operationalagent had not been able to set comprehensive and operational planning, and (5) Educational apparatuscould not practice qualified learning process.Key words: educational decentralization policy, legal framework, comprehensive planning.